1967
DOI: 10.1128/jb.94.4.1184-1188.1967
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Chemical Composition of the Cell Membranes of Developmental Reticulate Forms of Meningopneumonitis Organisms

Abstract: The outer limiting membranes of developmental reticulate forms of the meningopneumonitis organism were purified by a combination of differential centrifugation, trypsin digestion, and sodium dodecyl sulfate treatment, and their physical and chemical properties were compared with those of outer envelopes of mature dense forms of this organism. Reticulate bodies were easily disrupted by short periods of sonic treatment and were lysed by trysin digestion, in contrast to the dense bodies which were resistant to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…In Chlamydia, the signal for initiation of multiplication appears to be provided by host-generated reductants in the intracellular environment. Unlike most procaryotes, chlamydiae have no peptidoglycan layer in their cell envelopes (35,142), and the rigidity of the elementary body wall resides in large disulfide bond-linked complexes of the major outer membrane protein (37,178,182,302,398 Three lines of evidence suggest that this reduction increases the permeability of the elementary body envelopes to ATP and other nucleoside triphosphates which they need for reorganization into multiplying reticulate bodies. They are as follows: (i) host-free reticulate bodies, but not elementary bodies, transport ATP and other nucleoside triphosphates (178,179); (ii) isolated elementary bodies synthesize RNA from exogenous nucleoside triphosphates, but only after they have been treated with the reducing agent mercaptoethanol (397); and (iii) studies with liposomes made from chlamydial outer membrane complexes suggest that intact outer membanes have pores large enough to accommodate nucleoside triphosphates, but only when care is taken to avoid the formation of disulfide bond-linked complexes (37).…”
Section: Modification Of Host Cell Membranes Of the Parasites Ofmentioning
confidence: 99%
“…In Chlamydia, the signal for initiation of multiplication appears to be provided by host-generated reductants in the intracellular environment. Unlike most procaryotes, chlamydiae have no peptidoglycan layer in their cell envelopes (35,142), and the rigidity of the elementary body wall resides in large disulfide bond-linked complexes of the major outer membrane protein (37,178,182,302,398 Three lines of evidence suggest that this reduction increases the permeability of the elementary body envelopes to ATP and other nucleoside triphosphates which they need for reorganization into multiplying reticulate bodies. They are as follows: (i) host-free reticulate bodies, but not elementary bodies, transport ATP and other nucleoside triphosphates (178,179); (ii) isolated elementary bodies synthesize RNA from exogenous nucleoside triphosphates, but only after they have been treated with the reducing agent mercaptoethanol (397); and (iii) studies with liposomes made from chlamydial outer membrane complexes suggest that intact outer membanes have pores large enough to accommodate nucleoside triphosphates, but only when care is taken to avoid the formation of disulfide bond-linked complexes (37).…”
Section: Modification Of Host Cell Membranes Of the Parasites Ofmentioning
confidence: 99%
“…Trypsinization of [35S]cysteine-labeled EBs. Disulfide-mediated cross-linking of chlamydial outer membrane proteins (2,18,19,27) appears to confer structural rigidity to these gram-negative bacteria which lack demonstrable peptidoglycan (1,17,24,36). In addition, disulfide exchange of chlamydial proteins with eucaryotic cell components has been proposed as a mechanism potentially involved in the interactions of chlamydiae with host cells (18).…”
Section: 63mentioning
confidence: 99%
“…The developmental cycle of chlamydiae is complex, involving an extracellular infectious cell type, the elementary body (EB), and a metabolically active but noninfectious reticulate body that multiplies by binary fission (3,15,29). Chlamydiae resemble gram-negative bacteria in their cell wall structure but differ from them in that chlamydiae lack demonstrable peptidoglycan (1,17,24,36). It is believed that the structure conferring rigidity to the EB cell wall is a network of disulfide cross-linked outer membrane proteins (2,18,19,27).…”
mentioning
confidence: 99%
“…(1,4,10). Despite this apparent absence of peptidoglycan, the cell envelope of the chlamydial EB is characteristically rigid and is resistant to mechanical disruption, whereas that of the RB is relatively fragile (2,3,10,12,23 proposed that a protein or lipoprotein layer in the chlamydial cell envelope could be crosslinked through bridges between peptidoglycanlike tetrapeptides on adjacent proteins. However, supportive evidence for these hypotheses has not been described.…”
mentioning
confidence: 99%
“…However, supportive evidence for these hypotheses has not been described. Manire and Tamura (10,23) observed that EB cell walls possess cystine and methionine, whereas RB cell walls do not; Hatch et al (6) reported that envelope proteins of Chlamydia psittaci could only be solubilized by sodium dodecyl sulfate (SDS) in the presence of a reducing agent. Taken together, these ob-servations suggest that protein-protein interactions mediated by disulfide bonds could possibly play a role in the structure of EB cell walls.…”
mentioning
confidence: 99%